Queue Information System at One-Stop Integrated Services in the Ministry of Religion's Office of Dharmasraya Regency: Sistem Informasi Antrian Pelayanan Terpadu Satu Pintu Kantor Kementerian Agama Kabupaten Dharmasraya - Siska Emiliya; Wulan Andang Purnomo; Lido Sabda Lesmana; Gunawan Ali (Journal of Vocational Education and Information Technology (JVEIT), 2020)
The Office of the Ministry of Religion is one of the Government Agencies that has inaugurated the One-Stop Integrated Service. In a one-stop integrated service already using a computer as a data processing device, but based on observations of researchers the Office of the Ministry of Religion applies a queuing system manually where registration officials call verbally, so visitors want to overtake each other and inconvenience and lack of discipline is queued. And observations from researchers of the system are ineffective and cause complaints from visitors. To improve the quality of service to visitors, a desktop-based Queue Information System application is created using the java programming language. This program is expected to help improve services so as to create optimal service.